Lithium Niobate Metasurfaces. Issue 5 (7th April 2019) - Gao, Bofeng; Ren, Mengxin; Wu, Wei; Hu, Hui; Cai, Wei; Xu, Jingjun
Abstract: Lithium niobate is a multi‐functional material, which has been regarded as one of the most promising platforms for the multipurpose optical components and photonic circuits. Targeting miniature optical components and systems, lithium niobate microstructures with feature sizes of several to hundreds of micrometers are demonstrated, such as waveguides, photonic crystals, micro cavities, and modulators, and so on. In order to demonstrate the possibilities toward further shrinking the footprint of the lithium niobate devices with new optical functionalities, here, subwavelength nanograting metasurfaces are fabricated based on a crystalline lithium niobate film. Due to the collective lattice interactions between isolated ridge resonances, distinct transmission spectral resonances are observed, which could be tunable by varying the structural parameters. Furthermore, the metasurfaces are capable of showing high‐efficiency transmission structural colors as a result of structural resonances and intrinsic high transparency of lithium niobate in visible spectral range. The results pave the way for new types of ultracompact photonic devices based on lithium niobate. Abstract : Lithium niobate metasurfaces are fabricated experimentally. Distinct optical resonances are observed, which enable various novel nanophotonic applications of lithium niobate, such as high‐efficiency structural color.